Mixed methods for telehealth research. (October 2017) - Caffery, Liam J; Martin-Khan, Melinda; Wade, Victoria
Mixed methods research is important to health services research because the integrated qualitative and quantitative investigation can give a more comprehensive understanding of complex interventions such as telehealth than can a single-method study. Further, mixed methods research is applicable to translational research and program evaluation. Study designs relevant to telehealth research are described and supported by examples. Quality assessment tools, frameworks to assist in the reporting and review of mixed methods research, and related methodologies are also discussed.